Colorectal Cancer Stem Cells123. (14th February 2012) - Vaiopoulos, Aristides G.; Kostakis, Ioannis D.; Koutsilieris, Michael; Papavassiliou, Athanasios G.
Abstract: Colorectal cancer (CRC) is one of the most commonly diagnosed and lethal cancers worldwide. It is a multistep process that requires the accumulation of genetic/epigenetic aberrations. There are several issues concerning colorectal carcinogenesis that remain unanswered, such as the cell of origin and the type of cells that propagate the tumor after its initiation. There are two models of carcinogenesis: the stochastic and the cancer stem cell (CSC) model. According to the stochastic model, any kind of cell is capable of initiating and promoting cancer development, whereas the CSC model suggests that tumors are hierarchically organized and only CSCs possess cancer‐promoting potential. Moreover, various molecular pathways, such as Wingless/Int (Wnt) and Notch, as well as the complex crosstalk network between microenvironment and CSCs, are involved in CRC. Identification of CSCs remains controversial due to the lack of widely accepted specific molecular markers. CSCs are responsible for tumor relapse, because conventional drugs fail to eliminate the CSC reservoir. Therefore, the design of CSC‐targeted interventions is a rational target, which will enhance responsiveness to traditional therapeutic strategies and reduce local recurrence and metastasis. This review discusses the implications of the newly introduced CSC model in CRC, the markers used up to now for CSC identification, and its potential implications in the design of novel therapeutic approaches. STEM CELLS 2012;30:363–371